Philosophical view of the historical constitution of Bohr’s complementarity principle - Sánchez Ovcharov, Carmen (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2018)
This paper is a chronology of the theoretical proposals and experiments that led to Bohr's complementarity principle. This work exhibits how, under this principle, two classical models underlie: ondulatory and corpuscular. These are an analogy to describe and predict quantum phenomena. These models and mutually exclusive in both areas, classic and quantum. Nonetheless, the quantum phenomena require the application -though not simultaneously - of both to achieve the complete treatment. The question is whether the extrapolation of these models, in addition to their instrumental adequation, can be considered as close to reality.